Analysis of the Availability and Sustainable Management of Clean Water and Sanitation in Bogor Regency - Aminda, Renea Shinta (ASTONJADRO, 2024)
The provision of clean water includes several main components, including: raw water source unit, processing unit, production unit, transmission unit and production unit. Water is used by humans for various daily needs. Water needs for individual needs vary for each place and each level of need. The higher the standard of living in a place, the greater the need for water. The goal that must be achieved in managing clean water in stages is to have access to household drinking water services reaching 100% by 2030. The next achievement is the achievement and realization of sanitation and clean water management for vulnerable community groups at 68.77%, shown by this achievement in 2026. To achieve the number of sub-districts or villages implementing community-based total sanitation of 98%. Meanwhile, the achievement of the proportion of households served by a centralized clean water waste management system is 71.66% in 2026. The proportion of households served by a fecal sludge management system until this data is published has not been covered so the baseline set at 20% in 2021 will be achieved in 2023 The Bogor Regency Government's target in establishing this feces processing concept is very good.